Decision-making assessments in youth team invasion game athletes: A systematic scoping review - Inns, J.; Petancevski, E. L.; Novak, A. R.; Fransen, J. (International Journal of Sports Science & Coaching, 2023)
Decision-making is critical to team invasion game performance. As such, understanding how to measure and develop it is important to researchers and practitioners. However, due to the abundance of assessments available in this area, the optimal use of these assessments is still unclear. The current systematic scoping review summarises and examines the quality of reporting of the available literature on decision-making assessments that can be used in the context of youth team invasion games. It uses an ecological dynamics perspective to evaluate the extent to which the included decision-making tasks adhered to principles of representative task design, specificity of perception and action components and constraints present in each task. The results revealed that soccer was the most frequently studied invasion game (70% of studies). While realistic task (85% of studies) and individual constraints (68% of studies) were often present in decision-making tasks, environmental constraints received far less attention (9% of studies). About one-third of studies were situated on either end of the controlled laboratory in situ study continuum (controlled laboratory = 35%, in situ = 33%). In total, 39% of studies coupled sport-specific perception and action components. Furthermore, studies that implemented sport-specific perception-action coupling featured much smaller sample sizes than those without. The findings of this systematic review can aid researchers and practitioners who want to measure decision-making skill in youth team invasion game athletes by allowing them to make informed choices about which assessment to use based on the extent to which an assessment matches a set of pre-determined criteria.